MODEL PERENCANAAN PENGEMBANGAN WILAYAH AGRO INDUSTRI BERDASARKAN ANALISIS PENGINDERAAN JAUH DAN SIG - Arifin, Samsul (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
The policy of governmenr's economical agriculture is to emphasize on agriculture supported by the industry and vice versa. This is directed to increase the welfare of Indonesian people. One of the bridges that can connect the two things (agriculture and industry) is agro industry. The model of planning development of regional space system for argo industry has the porpose of arranging and planning food plantation argo-industry zone so that the condition of establishing an industry can be supported by the continuous availability of raw material that the carrying out of argo industry can be continuously and permanently. The applied approach to the forming of the model uses GIS with room analysis. The parameter used is land physical aspect parameter (land availability) and social economy. Research on the study case is carried out in Lampung Tengah Regency. Based on analysis of Lampung Tengah Regency, there are three argo industry zones that is paddy Argo industry zone located in Padang Ratu district, corn argo industry zone located in Gunung Sugih, and cassava argo industry zone located in Rumbia district.